MEMPERKUAT FUNGSI LEMBAGA PERLINDUNGAN SAKSI DAN KORBAN (LPSK ) DALAM PEMBERIAN PERLINDUNGAN DAN BANTUAN TERHADAP SAKSI DAN KORBAN - MANAMBUS PASARIBU (JURNAL ILMIAH SIMANTEK, 2020)
Regulation of Witness and Victim Protection are regulated in Law Number 13 of 2006 concerning Protection of Witnessesand Victims in conjunction with Law No. 31 of 2014 concerning Amendment to Law No. 13 of 2006 concerning Protection ofWitnesses and Victims. Both of these regulations give LPSK the authority to provide special protection for gross humanrights violations, terrorism, trafficking in persons, criminal acts of torture, sexual violence, and victims of serious abuse. Inaddition, the victim has the right to receive medical assistance and psychosocial and psychological rehabilitation.The role and urgency of the LPSK in providing protection and assistance to witnesses and victims is absolutely necessary.This is to guarantee the existence of efforts to protect witnesses who provide information in court. It is the adequaterecovery efforts to restore the victim's position to be normal.